On the unsteady behaviour of a liquid hydrogen fuel system pump for aircraft engine applications - Lamprakis, Dimitrios; Rajendran, David John; Yates, Martin; Roumeliotis, Ioannis; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2025)
The unsteady behaviour of a 2-stage liquid hydrogen (LH2) fuel system pump for future aircraft engine applications is investigated herein by means of full wheel, uRANS simulations. Compressibility, thermodynamic state and leakage flow effects are investigated to assess their individual contribution in the stability and unsteady pump operation. This is achieved by comparing three pump configurations along with two different modelling approaches: a baseline geometry without cavities, one with shroud cavities only, and a full model comprising all cavities, while real gas and constant propertyfluids are used to assess compressibility effects. An initial performance and component stability analysis is carried out using steady-state simulations and standard non-dimensional quantities. Unsteady simulations are subsequently performed combining the different modelling approaches and geometries at very low, off-design flow rates, representative of part-load operation. Unsteady signals are recorded at several planes in the pump flow path along with multiple monitor points around the annulus. These are then analysed in the frequency domain, providing a link between key flow features and the high-power frequency content. Compressibility effects are shown to slightly penalise the head rise of the pump without however penalising stability. The implications of the thermodynamic state of hydrogen on the transient pump response are minor, while the recorded head fluctuation amplitude of the baseline configuration reaches 18.4% of the mean value. Both impellers of the baseline configuration exhibit a mild surge-type of behaviour associated with stalled flow-induced blockage near the volute tongue resulting in heavy stalling of the splitter blades. Leakage flows negatively affect the steady-state pump performance but alleviate full and splitter blade stall, reducing the pump’s oscillation intensity by 30.6% through partial suppression of the stalled flow near the volute tongue. The study highlights the importance of transient performance in low-specific-speed hydrogen fuel pumps, as part-load operation may entail significant operability challenges.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; pump; aircraft; hydrogen; leakage; head; uRANS; instability; stall; surge